Morphological and Histopathological Changes in Orofacial Structures of Experimentally Developed Acromegaly-Like Rats: An Overview - Masahiro Iikubo; Ikuho Kojima; Maya Sakamoto; Akane Kobayashi; Hidetoshi Ikeda; Takashi Sasano (International Journal of Endocrinology)
Tongue enlargement and mandibular prognathism are clinically recognized in almost all patients with acromegaly. An acromegaly-like rat model recently developed by exogenous administration of insulin-like growth factor I (IGF-I) was used to investigate morphological and histopathological changes in orofacial structures and to clarify whether these changes were reversible. Exogenous administration of IGF-I evoked specific enlargement of the tongue with identifiable histopathological changes (increased muscle bundle width, increased space between muscle bundles, and increased epithelial thickness), elongation of the mandibular alveolar bone and ascending ramus, and lateral expansion of the mandibular dental arch. Regarding histopathological changes in the mandibular condyle, the cartilaginous layer width, bone matrix ratio, and number of osteoblasts were all significantly greater in this rat model. After normalization of the circulating IGF-I level, tongue enlargement and histopathological changes in the tongue and mandibular condyle were reversible, whereas morphological skeletal changes in the mandible remained.